The Relationship of the Health Belief Model to the Prevention Behavior of Metabolic Syndrome: A Meta-Analysis Study - Cendekia Airedeta Mulianda; Dena Tri Solehaini (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Risk factors for Metabolic Syndrome include hypertension, glucose intolerance, central obesity and dyslipidemia. These conditions if they occur together are referred to as Metabolic Syndrome which can increase the risk of non-communicable diseases, namely heart, stroke, and type 2 diabetes. This study aimed to estimated the relationship between the constructs of the Health Belief Model (HBM) on the prevention of metabolic syndrome (SM) risk factors.Subjects and Method: This article was compiled with a systematic review and meta-analysis study. This study uses the PICO Model. The meta-analysis study was conducted by searching for articles from databases in electronic form including Google Scholar, Pub-Med, and Science Direct. The keywords used are